Impact of acne vulgaris on self-esteem, body image perception and quality of life among adolescents - Yoqub, Fozia; Bajwa, Ruqia Safdar; Batool, Iram (Journal of Pakistan Association of Dermatologists, 2020)
Background Different aspects of oneâ€™s life like Self-Esteem, Body image perception and quality of life are adversely affected by Acne vulgaris. Although acne affects the majority of adolescents, but in order to check the impact of acne on self-esteem, body image perception and quality of life in this age group less data is currently available. Â Methods This study comprised of 250 member, they were of 10 to 18 years old with the issue of acne vulgaris. At that point their sexual orientations, age, acne seriousness level, living arrangement were gathered as demographic variables; and respondent were chosen through purposive testing procedure. Three scales were used to assess the variable of the study Body Image State Scale developed by Cash, (2005), Rosenberg Self-Esteem Scale grew by Rosenbery, (1965) and Quality of life Index Developed by Basra et al., (2008). The universe of the present study was Nishtar Hospital Multan. Â Results Significant positive correlation has been found between the body image perception and self-esteem among adolescents while the body image perception and quality of life among adolescents were also positively correlated. Results further revealed a significant positive correlation between the self-esteem and quality of life among adolescents. Self-esteem is moderate the body image perception and quality of life among adolescents. Â Conclusion This study concluded that the level of acne severity is directly associated with quality of life among adolescent and it also blow the self-esteem and body image perception of adolescents. Â